2022
DOI: 10.1159/000523751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Region-of-Interest Size on Immune Profiling Using Multiplex Immunofluorescence Tyramide Signal Amplification for Paraffin-Embedded Tumor Tissues

Abstract: <b><i>Introduction:</i></b> Representative regions of interest (ROIs) analysis from the whole slide images (WSI) are currently being used to study immune markers by multiplex immunofluorescence (mIF) and single immunohistochemistry (IHC). However, the amount of area needed to be analyzed to be representative of the entire tumor in a WSI has not been defined. <b><i>Methods:</i></b> We labeled tumor-associated immune cells by mIF and single IHC in separate coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We annotated a total of 1,076 ROIs from the mIF slides. The average ROIs per patient is 13.8, which is higher than the number of ROIs needed to achieve stable correlation compared to analyzing the entire slide demonstrated in prior work [23]. After cell segmentation, 3,229,582 cells were identified.…”
Section: Resultsmentioning
confidence: 97%
“…We annotated a total of 1,076 ROIs from the mIF slides. The average ROIs per patient is 13.8, which is higher than the number of ROIs needed to achieve stable correlation compared to analyzing the entire slide demonstrated in prior work [23]. After cell segmentation, 3,229,582 cells were identified.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, we originally selected 10 ROIs for analysis with the intent of expanding our understanding of the heterogeneity of the TME ( 53 ). Recent work from Sun et al., has shown that selection of 5 ROIs is able to reasonably recapitulate the TME in non-small cell lung cancer whole slide sections ( 60 ). The dependence on tissue availability and fluorescent probes that deviate from pathology standards are other technical limitations with mIF.…”
Section: Discussionmentioning
confidence: 99%
“…This approach uses TSA reagents, significantly increasing sensitivity while maintaining specificity and resolution, allowing detection in lowexpression targets [38,[40][41][42][43]. However, it is essential to select the areas that can represent the whole tumor section [44]. In the optimization process, cross-talking reactions or umbrella effects should be minimized or eliminated [34,37].…”
Section: Discussionmentioning
confidence: 99%